The Influence of Minimum Wages and Unemployment Rates on Poverty in Indonesia for the Period 2015-2025 - Muammar Rinaldi; Vivi Safira; Mentari Rezeki Ramadhani; Vingky Dwi Pratama; Zulfa Afifah (Outline Publisher, 2025)
This study aims to analyze the influence of minimum wages and unemployment rates on poverty levels in Indonesia during the period 2015–2024. Poverty remains one of the most persistent socio-economic challenges in developing countries, including Indonesia, where economic growth does not always lead to equitable welfare distribution. Minimum wage policies are expected to improve the income of low-income workers, while high unemployment rates tend to increase the number of people living below the poverty line. Therefore, understanding the interaction between these variables is essential for designing effective poverty reduction strategies. This research employs a quantitative approach using multiple linear regression analysis to examine the relationship between minimum wages, unemployment rates, and poverty levels. The study utilizes secondary data obtained from the Central Statistics Agency (Badan Pusat Statistik/BPS) covering the 2015–2024 period. Data were processed using statistical software to test both the partial and simultaneous effects of the independent variables on poverty. The results reveal that minimum wage and unemployment rate variables significantly affect poverty levels, both partially and simultaneously. However, the effect of minimum wage increases on reducing poverty is not always consistent, particularly when not accompanied by improvements in labor productivity and job creation. Conversely, the unemployment rate has shown a strong and positive relationship with poverty, indicating that higher unemployment tends to raise poverty levels. The findings highlight the importance of integrating wage policies with employment and productivity enhancement programs to achieve sustainable poverty reduction in Indonesia.